Physical activity and obesity research in the Asia-Pacific: a review - Khoo, Selina; Morris, T. (SAGE Publications, 2012)
Obesity is a global health concern and has a great impact on countries in the Asia-Pacific region. Physical inactivity is a major risk factor for obesity, but physical activity levels are declining in much of this region. Increasing physical activity is a priority in many countries. Considerable research has been conducted on physical activity related to obesity in Western countries, but populations in the Asia-Pacific region differ in physical, psychological, social, and cultural ways that warrant local and regional research. The authors reviewed research conducted in the Asia-Pacific region that examined either the impact of physical activity interventions on obesity-related outcomes or the effect of behavior-change interventions on physical activity participation. The number of studies found was limited, and their samples and methods varied too much to draw conclusions. The authors recommend further research in the Asia-Pacific region using systematic protocols to permit sound conclusions to be drawn and promote informed action at local levels.